Compatibility of 3D printing materials and printing techniques with PAGAT gel dosimetry. (8th February 2019) - Elter, A; Dorsch, S; Mann, P; Runz, A; Johnen, W; Karger, C P
Abstract: Polymer gel (PG) dosimetry enables three dimensional (3D) measurement of complex dose distributions. However, PGs are strongly reactive with oxygen and other contaminations, limiting their applicability by the need to use specific container materials. We investigate different 3D printing materials and printing techniques for their compatibility with PG. Suitable 3D printing materials may provide the possibility to perform PG dosimetry in complex-shaped phantoms. 3D printed and PG-filled test vials were irradiated homogenously. The signal response was evaluated with respect to homogeneity and compared to the signal in already validated reference vials. In addition, for the printing material VeroClear ™ (StrataSys, Eden Prairie, USA) different methods to remove support material, which was required during the printing process, were investigated. We found that the support material should be used only on the outer side of the container wall with no direct contact to the PG. With the VeroClear ™ material a homogenous signal response was achieved with a mean deviation of relative to the reference vials. In addition, the homogeneous irradiation of an irregularly-shaped gel container designed with the same printing material and technique also lead to a homogenous PG response. Furthermore, a small field irradiation of an additional test-vial showed an accurate representation of steep dose gradients with a deviation of the maximum position of relative to the reference vial.